Use the substitution method to find all solutions of the system of equations. \[ \begin{array}{r}x^{2}+y^{2}=49 \\ y=2 x\end{array} \] smaller \( x \)-value \( \quad \begin{array}{r}(x, y)=(\square)\end{array} \) \( \begin{array}{ll}\text { larger } x \text {-value } & (x, y)=(\square)\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the system of equations using the substitution method, we start with the equations: 1. \( x^2 + y^2 = 49 \) 2. \( y = 2x \) We can substitute \( y \) from the second equation into the first equation: \( x^2 + (2x)^2 = 49 \) This simplifies to: \( x^2 + 4x^2 = 49 \) \( 5x^2 = 49 \) Dividing both sides by 5 gives: \( x^2 = \frac{49}{5} \) Taking the square root of both sides, we find: \( x = \pm \sqrt{\frac{49}{5}} \) \( x = \pm \frac{7}{\sqrt{5}} = \pm \frac{7\sqrt{5}}{5} \) Next, we substitute these values back to find \( y \): For \( x = \frac{7\sqrt{5}}{5} \): \( y = 2x = 2 \cdot \frac{7\sqrt{5}}{5} = \frac{14\sqrt{5}}{5} \) For \( x = -\frac{7\sqrt{5}}{5} \): \( y = 2x = 2 \cdot -\frac{7\sqrt{5}}{5} = -\frac{14\sqrt{5}}{5} \) Thus, the solutions are: Smaller \( x \)-value: \( (x, y) = \left(-\frac{7\sqrt{5}}{5}, -\frac{14\sqrt{5}}{5}\right) \) Larger \( x \)-value: \( (x, y) = \left(\frac{7\sqrt{5}}{5}, \frac{14\sqrt{5}}{5}\right) \)